Information security and cryptology : 11th International Conference, Inscrypt 2015, Beijing, China, November 1-3, 2015 ; proceedings /: 11th International Conference, Inscrypt 2015, Beijing, China, November 1-3, 2015 ; proceedings. (2016) - Unknown
No abstract available